PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK KELAS X MIA 3 SMA NEGERI 2 SUKOHARJO TAHUN PELAJARAN 2015/2016 - Luciana Dwi Noma; Baskoro Adi Prayitno; Suwarno Suwarno (Universitas Sebelas Maret, 2016)
This research aimed to improve the high-order thinking ability of students by applying PBL model in Environment Pollution Material in10th MIA 3 graders of SMA Negeri 2 Sukoharjo in the school year of 2015/2016. This study was a classroom, action research use the procedure of research employed Kemmis and Mc.Taggart’s (2005) conducted in 2 cycles, from April to May 2016. Each cycle consisted of 4 stages: planning, acting, observing, and reflecting. Subject of research was the in10th MIA 3 graders of SMA Negeri 2 Sukoharjo in the school year of 2015/2016 consisting of 31 students (18 female and 13 male students). Data of research was obtained using essay test on the high-order thinking ability, interview, observation sheet on the implementation of PBL syntax, observation sheet on affective and psychomotor aspects of students. Essay test of high-order thinking ability includes indicators: analyzing (C4), evaluating (C5), and creating (C6) based on Bloom’s revised taxonomy. Data analysis was carried out using descriptive analysis technique. Data validation was carried out using triangulation technique. The target of research was the improvement of students’ high-order thinking ability in every aspect of ≥ 23% from based line to the end of research cycle. The result of research showed that the application of PBL model in environment pollution material could improve the high-order thinking ability of students including analyzing (C4), evaluating (C5), and creating (C6) aspects consistent with the target of research, by ≥23% from based line to the end of research cycle. The increase of percentage gain in each aspect of high-order thinking ability from precycle to cycle II was as follows: 1) the analyzing aspect increased by 25.16%, 2) the evaluating aspect increased by 26.66%, and 3) the creating aspect increased by 23.95%. Keywords : Problem Based Learning, high-order thinking, environment pollution.